Ferrocene functionalized graphene: preparation, characterization and application as an efficient catalyst for the thermal decomposition of TKX-50. Issue 32 (9th August 2021) - Zhang, Ming; Zhao, Fengqi; Li, Hui; Dong, Shuai; Yang, Yanjing; Hou, Xiaoting; An, Ting; Jiang, Zhoufeng
Abstract : A series of ferrocene functionalized graphene with different molecular structures were fabricated, characterized and used for the thermal decomposition of energetic TKX-50. Abstract : Novel ferrocene functionalized graphene with different molecular structures were designed, fabricated and characterized via SEM, EDS, FTIR, XPS and RAMAN methods. SEM results show the two-dimensional structure of the as-prepared catalysts, and the active metal Fe is uniformly distributed on the surface of graphene. The FTIR, XPS and RAMAN results confirmed the successful preparation of ferrocene functionalized graphene. The catalytic effects of the as-synthesized catalysts for the thermal decomposition of energetic TKX-50 were monitored by DSC, and the corresponding kinetic parameters were calculated using multi kinetic methods including traditional and nonlinear models. The results showed that the as-prepared ferrocene functionalized graphene can effectively promote the thermal decomposition of TKX-50 with the reduced decomposition peak temperatures and activation energies. In addition, the effects of ferrocene functionalized graphene for TKX-50 decomposition are reflected in both high and low temperature stages, and the effect on the high temperature stage is more significant. The outstanding catalytic activity of ferrocene functionalized graphene is related not only to the good dispersion of active Fe, but also to the enhanced interaction of small molecule products on two-dimensional graphene. Among the ferrocene functionalized graphene studied, G-792-Fe and G-902-Fe exhibit better catalytic effects on the thermal decomposition of TKX-50, which can be used as candidate catalysts for TKX-50-based solid propellants.